Preoperative predictors of thrombocytopenia in Caesarean delivery: is routine platelet count testing necessary?. (2nd November 2017) - Nkomentaba, Lulama; Bishop, David G; Rodseth, Reitze N
Abstract: Background: Peri-partum thrombocytopenia significantly impacts anaesthetic technique and increases the risk of perioperative bleeding. However, as less than 5% of normal pregnancies have significant thrombocytopenia, routine platelet testing incurs great cost for a relatively low yield. Determining whether clinical predictors, in particular HIV status, are associated with thrombocytopenia may assist clinicians in rationalising preoperative testing. Methods: This was a prospective, observational, single-centre study at a South African regional hospital. We evaluated five variables as candidate predictors for mild preoperative thrombocytopenia (< 150 000/μl) in patients scheduled for both elective and emergency Caesarean delivery: HIV status, pre-eclampsia, urgency of surgery, renal impairment and liver failure. As a sub-analysis we compared the incidence of moderate thrombocytopenia (< 100 000/μl) in HIV-positive patients, with HIV-negative patients. Results: We recruited 1 015 patients to this study. The incidence of mild thrombocytopenia was 10.3% (105/1 015). Only pre-eclampsia was predictive of mild thrombocytopenia (odds ratio 3.51; p < 0.01; 95% confidence interval 2.12–5.82). The incidence of moderate thrombocytopenia was not influenced by HIV status (occurring in 1.5% of HIV-positive patients versus 1.8% in HIV-negative patients; p = 0.716). Conclusions: In this study of predominantly asymptomatic patients scheduled for Caesarean delivery, only pre-eclampsia was predictive of mild thrombocytopenia. In sub-analysis HIV status was not independently associated with moderate thrombocytopenia. All asymptomatic patients, including those who were HIV positive, had platelet counts > 70 000/μl.